214k views
1 vote
Simplify fully
4x^2+4x/2x^2-2

User Dave Cook
by
4.8k points

2 Answers

0 votes

Answer:

the answer i got is 2 (x+1) (2x^2-2x+1) / x :)

User Bengerman
by
4.7k points
6 votes

Answer:


(2x)/(x-1)

Explanation:


(4x^2+4x)/(2x^2-2) ← factor numerator and denominator

=
(4x(x+1))/(2(x^2-1)) ← cancel 4 and 2 on numerator/denominator by 2

=
(2x(x+1))/(x^2-1) ← x² - 1 is a difference of squares

=
(2x(x+1))/((x-1)(x+1)) ← cancel (x + 1) on numerator and denominator

=
(2x)/(x-1)

User MobileVet
by
4.4k points